Radial and tibial bone indices in athletes participating in different endurance sports: a pQCT study - Oosthuyse, T.; McVeigh, Joanne; Micklesfield, L.; Meiring, R. (Taylor and Francis Group, 2016)
Low magnitude bone-loading sports may benefit bone structure and strength in the exercised limbs. This study compared peripheral quantitative computed tomography measures of radial and tibial diaphyseal strength (strength–strain index, SSI), structure (total area (ToA) and cortical area (CoA), density (CoD) and thickness (CT), and circumferences), muscle cross-sectional area (MCSA) and strength (one-repetition maximum, 1-RM) in male endurance athletes taking part in (i) non-weight-bearing and non-impact sports: swimmers (SWIM, n = 13) and road cyclists (RC, n = 10), (ii) non-weight-bearing, impact sport: mountain bikers (MB, n = 10), (iii) weight bearing and impact sport: runners (RUN, n = 9). All athlete groups were also compared to sedentary controls (CON, n = 10). Arm MCSA, 1-RM and radial bone size and strength tended to be greater in SWIM than CON and/or RC (ToA, %difference ± 95%CI, SWIM-CON: 14.6% ± 12.7%; SWIM-RC: 12.9% ± 10.7%) but not different to MB and RUN. RUN had bigger tibial CoA than CON, SWIM and RC (CoA, RUN-CON: 12.1% ± 10.7%; RUN-SWIM: 10.9% ± 9.4%; RUN-RC: 15.8% ± 9.5%) without marked changes in tibial strength indices, lower-limb MCSA or 1-RM. Both MB and RC failed to display any difference in tibial indices, lower-limb MCSA and 1-RM compared to CON. In swimmers, the bone structure and strength of the primary exercised limbs, the arms, is greater than controls and road cyclists. Conversely, although runners experience impact and weight-bearing loading, tibial structure is greater without a substantial difference in tibial strength compared to controls and non-impact sports. Failure to observe a difference in tibial indices in MB and RC compared to controls is unexpected.